Lookback supports semi-parallel, just-in-time processing in second language written composition - Evgeny Chukharev; Jens Roeser; Mark Torrance (PLoS ONE, 2025)
Purpose Competent written production results from semi-parallel processes that flow from content determination to finger movement. Information from upstream processes that is not used immediately is easily lost. This disruption is more likely when a writer composes in a language in which they lack expertise (L2) than when they compose in their first language (L1). Looking back into text-just-written may serve to maintain fluent processing. Our research determined whether patterns of hesitation (pausing) and lookback in L1 and L2 writing were consistent with this theory. Method 39 university students composed argumentative texts by keyboard in L1 (English) and L2 (non-expert Spanish). Participants’ keystrokes were logged, and eye movements were tracked to determine when they looked back into their already-written text, and what text was fixated. Analysis focused just on cases where hesitation occurred in the absence of error correction. Results Students hesitated more frequently and for longer when writing in L2. Lookback in L2 was more common and deeper within existing text before and within words. Lookback at start of sentences was relatively frequent in both L1 and L2, but more extensive in L2. Conclusion Findings are consistent with lookback serving to refresh memory for what to write next.